Balloons larger than 15 mm can increase the risk of adverse events following endoscopic papillary large balloon dilation. Issue 8 (16th July 2019) - Lee, Gil Ho; Yang, Min Jae; Kim, Jin Hong; Hwang, Jae Chul; Yoo, Byung Moo; Lee, Dong Ki; Jang, Sung Ill; Lee, Tae Hoon; Park, Sang‐Heum; Park, Jin‐Seok; Jeong, Seok; Lee, Don Haeng
Abstract: Background and Aim: Although endoscopic papillary large balloon dilation (EPLBD) has been widely used to facilitate the removal of difficult common bile duct stones, however, the outcomes have not yet been investigated in terms of the diameter of the balloon used. We aimed to compare the clinical outcomes between EPLBD using smaller (12–15 mm, S‐EPLBD) and larger balloons (> 15 mm, L‐EPLBD). Methods: Six hundred seventy‐two patients who underwent EPLBD with or without endoscopic sphincterotomy for common bile duct stone removal were enrolled from May 2004 to August 2014 at four tertiary referral centers in Korea. The outcomes, including the initial success rate, the success rate without endoscopic mechanical lithotripsy, the overall success rate, and adverse events between S‐EPLBD and L‐EPLBD groups, were retrospectively compared. Results: The initial success rate, the success rate without mechanical lithotripsy, the overall success rate, and the overall adverse events were not significantly different between the two groups. The rate of severe‐to‐fatal adverse events was higher in the L‐EPBLD group than in the S‐EPLBD group (1.6% vs 0.0%, 0.020). One case of severe bleeding and two cases of fatal perforation occurred only in the L‐EPLBD group. In the multivariate analysis, the use of a > 15‐mm balloon was the only significant risk factor for severe‐to‐fatal adverse events (>0.005, 23.8 [adjusted odds ratio], 2.6–214.4 [95% confidence interval]). Conclusions: L‐EPLBD is significantly related to severe‐to‐fatal adverse events compared with S‐EPLBD for common bile duct stone removal.